U C Berkeley Co-op Friends Annual Heavy-Sacramento - Watkins, Howard::::::::: (1983)
Dale Mesple, Frank Gumpert, Janie Gumpert, Kathy Muniz, ?, Teresa Pricco, ? Terri Mesple, Jerry Neary, David Atkinson